PENGEMBANGAN E-MODUL MENGGUNAKAN APLIKASI FLIP PDF CORPORATE BERBASIS RADEC BERBANTUAN MIND MAP PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELAS V SD - Azzahidatul Hasanah; Risda Amini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by technological advances that give birth to innovations in learning. One of the innovations in learning is in terms of teaching materials that support students to learn independently, can be used anytime and anywhere, then adjust the needs and characteristics of students. Based on the results of observations that have been carried out in 4 schools, namely SDN 02 Lubuk Alung, SDN 15 Lubuk Alung, SDN 17 Lubuk Alung and SDN 04 Enam Lingkung, it was found that almost the same problem is that the school still does not utilize technology to the fullest. Schools still use teaching materials or printed modules that are not equipped with animations, pictures and videos so that students feel bored easily. Learning is still teacher-centered until it is monotonous. To overcome this, an E-Module was developed using a RADEC-based Flip PDF Corporate application assisted by mind maps on the human digestive system material in grade V of elementary school. This research aims to develop an E-Module using a RADEC-based Flip PDF Corporate application assisted by mind maps on valid and practical human digestive system materials. The research method used is Research and Development with the ADDIE model, which includes analysis, design, development, application, and evaluation. The validity test by material, media and language experts was declared to be very valid with an average validator score of 93.33%. Based on the teacher's response and the response of students at 2 school The trial showed that the E-Module was very practical in learning with an average of 92.5% and 96.4%. Meanwhile, the percentage of responses of teachers and students in research schools to E-Modules is very practical with an average of 97.5% and 96.8%. So it can be concluded that the E-Module using the RADEC-based Flip PDF Corporate application assisted by mind map on the human digestive system material in grade V elementary school is very valid and very practical to use in learning.